Football recovery strategies - Practical aspects of blending science and reality - Dupont, G.; Nedelec, M.; McCall, A.; Berthoin, S.; Maffiuletti, N. A. (ASPETAR Sports Medicine Journal, 2015)
In elite soccer, the number of competitive matches per season, including domestic, continental and international matches, can be very high for successful teams. Some players can play up to 70 competitive matches per season. In these conditions, the number of weeks with two matches per week is greater than the number of weeks with one match per week.